Hydrotreatment of pyrolysis liquids derived from second-generation bioethanol production residues over NiMo and CoMo catalysts. (July 2019) - Priharto, Neil; Ronsse, Frederik; Prins, Wolter; Hita, Idoia; Deuss, Peter J.; Heeres, Hero Jan
Abstract: Lignin-rich digested stillage from second-generation bioethanol production is a unique biomass-derived feedstock, not only because it contains high amounts of lignin but also due to its residual amounts of cellulose and hemicellulose. In this study, catalytic hydrotreatment experiments were conducted on pyrolysis liquids obtained from the lignin-rich feedstock using sulphided NiMo/Al2 O3 and CoMo/Al2 O3 catalysts. The aim was to obtain a high conversion of the initial pyrolysis feed into a hydrotreated oil with a high phenolics and aromatics fractions. Experiments were carried out in a stirred batch reactor at 350 °C and 10 MPa of H2 (initial pressure). Product oils were obtained in about 60–65% w/w, the remainder being an aqueous phase (12–14% w/w), solids (7–8% w/w) and gas phase components (all on initial pyrolysis oil feed basis). The product oils were characterised in detail using various techniques (elemental composition, GCxGC-FID, GPC, and 2D HSQC NMR). The oxygen content was reduced from 23% w/w in the pyrolysis oils to 7.5–11.5% in the hydrotreated oils, indicative of the occurrence of hydrodeoxygenation reactions. This was also evident from the chemical composition, showing an increase in the amounts of low molecular weight aromatics, alkylphenolics, alkanes and cycloalkanes in hydrotreated oils. Performance of the two catalysts was compared, and a higher degree of deoxygenation was observed for the NiMo catalyst. The implications of the findings for the valorisation of second-generation bioethanol residues are also discussed. Highlights: Hydrotreatment of pyrolysis liquids from second generation bioethanol residues was investigated. Sulfided NiMo and CoMo catalysts on alumina were used. Hydrotreated oil yields up to 65% w/w on feed were obtained. Hydrotreated oils were enriched in monomeric alkylphenolics and aromatics. Levels of deoxygenation were slightly higher for the NiMo catalyst.